The Ogiek Case and the African Court on Human and Peoples’ Rights: Strengthening the Rights of Indigenous Communities in Africa - Iglesias Vázquez, María Del Ángel (2018)
On May 26, 2017, the African Court on Human and Peoples' Rights (CAfDHP[1]) delivered its judgment in case 006/2012 (the African Commission on Human and Peoples' Rights (ACHPR) against the Republic of Kenya) declaring the massive and serious violation of rights, recognized in the 1981 African Charter on Human and Peoples' Rights, by the Republic of Kenya in favor of the Ogiek community. This decision comes after eight years of struggle. Previously, the system for the protection of the rights of indigenous communities in the African continent had been strengthened by the recommendation of November 25, 2009, of the African Commission on Human and Peoples' Rights in Case 276/03 (Center for Minority Rights Development (Kenya) and Minority Rights Group on behalf of the Endorois Welfare Council/Kenya) where an important doctrine is established about the fundamental rights of these communities, especially with regard to the ownership of ancestral lands and the spiritual meaning of them. Now, in the case of the Ogiek, the court is pronouncing, for the first time, on the violation of the rights contained in the African Charter, with respect to these indigenous communities, in a case whose plaintiff is precisely the African Commission on behalf of this group. This paper highlights some statements made by the Court, both with respect to the consideration of minorities and indigenous communities in general, and with respect to the scope or meaning of their ownership (in reinforcing their rights) and of the territorial integrity of the state in particular.